An updated map of Trypanosoma cruzi histone post-translational modifications - Rafael Fogaça de Almeida; Matheus Fernandes; Lyris Martins Franco de Godoy (Scientific Data, 2021)
Measurement(s) histone_modification Technology Type(s) mass spectrometry • nanoflow liquid chromatography-tandem mass spectrometry • Data-Dependent Acquisition Sample Characteristic - Organism Trypanosoma cruzi Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13491165